Characterization of the Interfacial Defect Layer in Chalcopyrite Solar Cells by Depth‐Resolved Muon Spin Spectroscopy. Issue 19 (7th June 2022) - Alberto, Helena V.; Vilão, Rui C.; Ribeiro, Eduardo F. M.; Gil, João M.; Curado, Marco A.; Teixeira, Jennifer P.; Fernandes, Paulo A.; Cunha, José M. V.; Salomé, Pedro M. P.; Edoff, Marika; Martins, Maria I.; Prokscha, Thomas; et al.
Abstract: As devices become smaller and more complex, the interfaces between adjacent materials become increasingly important and are often critical to device performance. An important research goal is to improve the interface between the absorber and the window layer by inserting buffer layers to adjust the transition. Depth‐resolved studies are key for a fundamental understanding of the interface. In the present experiment, the interface between the chalcopyrite Cu(In, Ga)Se2 absorber and various buffer layers are investigated using low‐energy muon spin rotation (μSR) spectroscopy. Depth resolution in the nm range is achieved by implanting the muons with different energies so that they stop at different depths in the sample. Near the interface, a region about 50 nm wide is detected where the lattice is more distorted than further inside the absorber. The distortion is attributed to the long‐range strain field caused by defects. These measurements allow a quantification of the corresponding passivation effect of the buffer layer. Bath‐deposited cadmium sulfide provides the best defect passivation in the near interface region, in contrast to the dry‐deposited oxides, which have a much smaller effect. The experiment demonstrates the great potential of low energy μSR spectroscopy for microscopic interfacial studies of multilayer systems. Abstract : The interface region between the Cu(In, Ga)Se2 (CIGS) solar cell absorber and the buffer layer, is investigated using implanted muons as local probes, deposited in the sample at different depths. Results show that a region near the interface (region 2) is more disturbed than the inner part of CIGS. Cadmium sulfide as a buffer reduces the disturbance more than oxide layers.